A review of tactical optimization models for integrated production and transport routing planning decisions. (October 2015) - Díaz-Madroñero, Manuel; Peidro, David; Mula, Josefa
Highlights: Review of tactical optimization models. Integrated production and transport routing planning. Identify current trends and future research. Propose a classification framework. Abstract: This paper presents a review of tactical optimization models for integrated production and transport routing planning decisions. The objective of this research is to identify current trends and future research directions in this field, and to propose a classification framework based on the following elements: production, inventory and routing aspects, modelling aspects of the objective function structure and solution approach. All these criteria are expected to be relevant for readers, and will provide researchers and practitioners a starting point for optimization models in the production and routing area at the tactical level.